Food, Photographs, and Frames: Photo Elicitation in a Canadian Qualitative Food Study - Sharma, Sonya; Chapman, Gwen (Cuizine)

(untitled) (McGill University Library, 2011)
Photo elicitation was employed in a cross-Canada study on family food habits as a means of understanding the meanings that people associate with food. From each family who took part in the study, at least one parent and one adolescent were asked to participate in a qualitative interview, to take photographs of how food fits into their everyday lives, and to participate in a second interview about their photos. In using photo elicitation, we were interested in ways in which participants eat, cook, and shop for food—everyday activities that are often taken for granted. In this article, we examine photographs and interview data provided by two mothers from the same rural community. We explore what their words and photographs reveal about their food worlds, both as self-representations reflecting the food environments in which they are embedded, and as the frames through which those environments are subsequently viewed and constructed.